Inovasi Virtual Reality (VR) sebagai Media yang Efektif pada Pembelajaran Sejarah Kebudayaan Islam - Baroroh, Rizqi Nailul; Zulfitria, Zulfitria; Rohmah, Ahmad Jamal (Universitas Garut, 2024)
The industrial revolution 5.0 is a fundamental thing that provides changes in how we socialize, work and also carry out daily activities. This virtual world with connections between three variables, namely data, machines and humans, is what is called the Internet of Things (IoT). This provides an opportunity for humans to take advantage of it by creating various kinds of media in life, especially in the world of education. Schools as a forum for facilitating various kinds of media that are developing and keeping up with the times in order to give birth to a superior generation, must provide various kinds of creative and innovative media. One of the media that can be used is virtual reality (VR). Learning media using virtual reality (VR) is an alternative solution to provide new and fun learning practices for students. virtual reality (VR) presents interesting videos and images with an adjustable time duration. This media can be used in several lessons such as the history of Islamic culture. Lessons that are considered difficult and boring can be overcome if there is supportive learning media, so as to create an active and enjoyable learning atmosphere. With a wise approach, virtual reality (VR) can be a medium that supports the educational process and improves the quality of education in the digital era